Distinguishing Affective Temperament Profiles in Major Depressive Disorder and Bipolar Disorder Through the Short Version of TEMPS-A: Cross-Sectional Study Using Latent Profile Analysis - Jang, Ha Lim; Lee, Chanhui; Yu, Hyeona; Lee, Daseul; Lee, Hyuk Joon; Ha, Tae Hyon; Kang, Hyo Shin; Myung, Woojae; Park, Jungkyu (Psychiatry investigation, 2024)
Objective This study aimed to elucidate the distinct response patterns exhibited by patients diagnosed with bipolar disorder (BD) and those with major depressive disorder (MDD) through the application of the short version of the Temperament Evaluation of Memphis, Pisa, Paris, and San Diego Autoquestionnaire (TEMPS-A-SV).Methods A total of 2,458 participants consisting of patients with MDD (n=288), BD (BD I, n=111; BD II, n=427), and control group (n=1,632) completed the TEMPS-A-SV. The response patterns of the participants were classified into distinct profiles using latent profile analysis. The study further examined the impact of covariates such as age, sex, and diagnostic group on derived latent profile memberships.Results The following three latent profiles were identified: High Affective Temperament Group (17.86%), Low Affective Temperament Group (41.25%), and Middle Affective Temperament Group (40.89%). Compared with the patient group with MDD and BD, the control group was more likely to belong in the Low Affective Temperament Group, which showed a higher score on hyperthymic temperament than the Middle Affective Temperament Group. Furthermore, compared with the patients with BD, the MDD patients were more likely to be in the Low Affective Temperament Group rather than the Middle Affective Temperament Group.Conclusion These results indicate that different affective temperaments exist between patients with MDD and BD. Attempting to classify response patterns using the TEMPS-A-SV can help diagnose MDD and BD correctly.